Single-Cell Transcriptomic Atlas of Primate Ovarian Aging. Issue 5 (May 2020) - Wang, Si; Zheng, Yuxuan; Li, Jingyi; Yu, Yang; Zhang, Weiqi; Song, Moshi; Liu, Zunpeng; Min, Zheying; Hu, Huifang; Jing, Ying; He, Xiaojuan; Sun, Liang; et al.
Abstract : (Abstracted from Cell 2020;180(3):585–600.e19) Age-associated declines in female fertility evident after only 30 years of age involve a decrease in total follicle number and oocyte quality. In addition, physiologic age–related changes include increased fibrosis, expanded stromal cell compartment, and changed ovarian medullary and cortex volume.